Relationship between Fault Level and System Strength in Future Renewable-Rich Power Grids - Aljarrah, Rafat; Karimi, Mazaher; Marzooghi, Hesamoddin; Alnaser, Sahban; Al-Omary, Murad; Salem, Qusay; Harasis, Salman (MDPI, 2022)
The fault level is used as a simple indicator for scanning the system strength in power systems. To an extent, this has proven its efficacy in classical power systems based on synchronous generation (SG). However, power electronics-based renewable energy sources (RESs), due to their controlled and limited fault current contribution, may affect the impedance, fault level, and system strength in a non-linear manner. Hence, this raises a question about the validity of using the fault level as a measure reflecting the system strength in future grids. This paper intends to shed light on the above question by examining the correlation between the fault level and the system strength in future grid scenarios. This is achieved in two steps: first, by employing the measure-based Thevenin impedance for fault level estimation in renewable-rich grids, and second, by comparing these estimated fault levels with those obtained from steady-state and dynamic simulations. While the results have demonstrated the suitability of using the fault level for system strength scanning in scenarios of low penetration of RESs, they revealed that such a tool might be misleading with very high RES penetrations. The findings have been verified using the adjusted IEEE nine-bus test system in DIgSILENT PowerFactory.
Keywords: fault level; system strength; Thevenin impedance; renewable energy sources; fi=Sähkötekniikka|en=Electrical Engineering|